Hemigrammus tridens Eigenmann (Characiformes, Characidae): First records of a small tetra from the Paraná River basin - Azpelicueta, Maria de Las M. (2017)
Hemigrammus tridens is a small characid described by Eigenmann (in Eigenmann & Ogle, 1907) from Paraguay River, in the country Paraguay. The species has a conspicuous trident-shaped caudal spot, few perforated lateral line scales, scales on the caudal fin, and two pentacuspidate teeth in the outer series of the premaxilla. Hemigrammus tridens is found in the Paraná River basin of both, Argentina and Paraguay. The records from Argentina are the first for this species in the country. Comments on the type series are added.